Assessing legislative gaps in Qatari law regarding AI-driven misinformation: insights from the UAE legal framework - Mashaallah Othman Alzwae; Abdelnaser Aljahani; Zinah Younus (Legality : Jurnal Ilmiah Hukum, 2025)
This study aims to examine the weaknesses of Qatari laws and assess their effectiveness in combating this new type of crime by comparing them with the UAE's Anti-Rumours and Cybercrime Law No. 34 of 2021, Article 54”, as a strong example of legislation in this area. The study highlights Singapore's law as a Southeast Asian example that explicitly criminalises "the creation or modification of robots as an artificial intelligence system used to spread misinformation," similar to the UAE law, indicating that the UAE law is more effective and comprehensive in combating these crimes. The study adopts a comparative analytical approach, which is the most appropriate approach to addressing emerging legal issues, such as those linked to the utilisation of AI systems to spread misleading content. The findings reveal weak Qatari legislative protection in this area, pointing to the need to reform the Anti-Cybercrime Law No. 14 of 2014. This law explicitly defines bots, rumours, and misinformation, and criminalises the act of "creating or modifying an electronic bot intended to publish, republish, or circulate misleading information in the country, or enable any other person to publish, circulate, or republish such information, or delete an electronic bot after committing a crime with the intent to mislead justice." It also revisits traditional criminal liability rules to align Qatari legislation with relevant international standards and Qatar's Artificial Intelligence Strategy.